Characterization of monolithic CMOS pixel sensor chip with ion beams for application in particle computed tomography - Tambave, Ganesh; Alme, J.; Barnaföldi, G. G.; Barthel, R.; van den Brink, A.; Brons, S.; Chaar, M.; Eikeland, V.; Genov, G.; Grøttvik, O.; Pettersen, H. E. S.; Pastuovic, Z.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2020)
Particle computed tomography (pCT) is an emerging imaging modality that promises to reduce range uncertainty in particle therapy. The Bergen pCT collaboration aims to develop a novel pCT prototype based on the ALPIDE monolithic CMOS sensor. The planned prototype consist of two tracking planes forming a rear tracker and Digital Tracking Calorimeter (DTC). The DTC will be made of a 41 layer ALPIDE-aluminum sandwich structure. To enable data acquisition at clinical particle rates, a large multiplicity of particles will be measured using the highly-granular ALPIDE sensor. In this work, a first characterization of the ALPIDE sensor performance in ion beams is conducted. Particle hits in the ALPIDE sensor result in charge clusters whose size is related to the chip response and the particle energy deposit. Firstly, measurements in a 10 MeV 4He micro beam have been conducted at the SIRIUS microprobe facility of ANSTO to investigate the dependence of the cluster size on the beam position over the ALPIDE pixel. Here, a variation in cluster size depending on the impinging point of the beam was observed. Additional beam tests were conducted at the Heidelberg Ion-Beam Therapy Center (HIT) investigating the cluster size as a function of the deposited energy by protons and 4He ions in the sensitive volume of the ALPIDE. Results show the expected increase in cluster sizes with deposited energy and a clear difference in cluster sizes for protons and 4He ions. As a conclusion, the variation in cluster size with the impinging point of the beam has to be accounted for to enable accurate energy loss reconstruction with the ALPIDE. This does, however, not affect the tracking of particles through the final prototype, as for that only the center-of-mass of the cluster is relevant.
Available online 26 August 2019
Gesehen am 07.04.2020